2020
DOI: 10.1186/s12884-020-03429-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality among neonates admitted to a special care unit in a low-resource setting

Abstract: Background Although under-5 mortality has decreased in the last two decades, neonatal mortality remains a global health challenge. Despite achieving notable progress, Ethiopia has still one of the highest neonatal mortality rates worldwide. We aimed to assess the risk factors for mortality among neonates admitted to a special care unit in a referral hospital in rural Ethiopia. Methods This was a retrospective observational study including all 4182 neonates admitted to the special care unit of the St. Luke Wol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The odds of neonatal mortality among referred neonates were almost five times higher compared to neonates who were not referred. This finding was similar to the results of a study done in India, a low resource setting, and Ethiopia (43)(44)(45). This might be due to delays in deciding to seek care, delay in reaching a first referral level facility, and delay in actually receiving care after arriving at the facility.…”
Section: Discussionsupporting
confidence: 91%
“…The odds of neonatal mortality among referred neonates were almost five times higher compared to neonates who were not referred. This finding was similar to the results of a study done in India, a low resource setting, and Ethiopia (43)(44)(45). This might be due to delays in deciding to seek care, delay in reaching a first referral level facility, and delay in actually receiving care after arriving at the facility.…”
Section: Discussionsupporting
confidence: 91%
“…In Ethiopia, a retrospective observational study over a 3-year period showed a death rate of 709 of 4182 (19%) in hospitalised neonates. 18 Here, risk factors for death included infants transported from home/other facilities, an inverse correlation between birth weight and risk of death, and an association between death and congenital malformations. The presence of intrapartum-related complications, likely analogous to HIE, was also a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of intrapartum-related complications, likely analogous to HIE, was also a risk factor. 18 In Uganda, one study demonstrated a mortality rate for all infants in a special care baby unit as 22.1%, with prematurity and its complications accounting for the majority of deaths. 19 However, in Eritrea, a study in a similar NNU revealed a death rate of 66 per 1000 live births despite similar burden of sepsis and comparable population characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in the special care unit of the St Luke Wolisso Hospital, which is a private referral, non‐profit hospital in the town of Wolisso in the Oromia region of Ethiopia. Around 1.2 million people live in this area, which is served by the Hospital and 80 health facilities 13 . The special care unit comprises one room with 14 beds, with three nurses on the morning, afternoon and night shifts and a paediatrician or medical officer on rotation duty.…”
Section: Methodsmentioning
confidence: 99%
“…Around 1.2 million people live in this area, which is served by the Hospital and 80 health facilities. 13 The special care unit comprises one room with 14 beds, with three nurses on the morning, afternoon and night shifts and a paediatrician or medical officer on rotation duty. Phototherapy, intravenous therapies and oxygen supplementation are offered, but pulse oximetry is limited.…”
Section: Settingmentioning
confidence: 99%